Epidemiology, Transmission, and Evolution of Japanese Encephalitis Virus - Chengcheng Peng; Huiling Qin; Fan Yu; Yujia Hao; Yuge Yuan; Wenzhou Ma; Duo Zhang; Pengpeng Xiao; Nan Li (Microorganisms)
The Japanese encephalitis virus is an arbovirus that causes severe damage to the central nervous system. At present, there are still 67,900 cases of Japanese encephalitis worldwide every year, which poses a global public health concern and causes great economic losses to animal husbandry. In this study, we analyzed the epidemiology, transmission, and evolution of JEV based on the NCBI database. E and NS1 were emphatically analyzed for amino acid variation and predicted protein structure. Gene recombination and the evolutionary rate of JEV were analyzed using RDP 4 and BEAST. The maximum clade credibility tree of E was reconstructed to estimate the time of the most recent common ancestor. Chinese genotype Ⅰ (GI) strain recombination events occurred in the C, M/PrM, E, NS2A, NS4B, and NS5 proteins, and genotype III (GIII) strains occurred in the E, NS1, NS3, NS4A, and NS5 proteins. The average evolutionary rates of JEV were comparable (3.3830 × 10−4, 2.0481 × 10−4, 3.5650 × 10−4, 2.2423 × 10−4, 3.0844 × 10−4, and 1.9757 × 10−4 substitutions/site/year for the JEV-I whole genome, JEV-III whole genome, JEV-I E gene, JEV-III E gene, JEV-I NS1 gene, and JEV-III NS1 gene, respectively). The MCC tree revealed the evolutionary order was GⅢ, GⅠ, GⅤ, GⅡ, and GⅣ. This study was expected to provide theoretical support for vaccine development and comprehensive prevention and treatment of JEV.